ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRILAKU KONSUMEN TERHADAP PRODUK CAFETY WELING DAFAZ MAKMUR JAKARTA - Arsid, Arsid (Cakrawala Akuntansi & Manajemen, 2024)
The regression coefficient of goods delivery (X4) on customer satisfaction is 921. ‘2, Library Research (library research) In this study the authors read books that have to do with customer satisfaction. In the development of the business environment, there are more and more diverse products offered by companies in the same industry, which is part of a product development strategy that aims to create consumer behaviour. Descriptive method used to describe, examine and analyse the relationship between consumer satisfaction (sarisfaction) in decision-making considerations and search information on cafety welding products. This shows a very strong and positive relationship between product quality ‘price’ sales service, delivery of goods and technical assistance together on customer satisfaction. Delivery of goods has a significant effect on customer satisfaction, because it is calculated at 8,686 with a significance of 0.000 less than the probability of 0.05.